Can Universities Be Considered Queer Institutions? - Pilkington, Scott; Eklund, Tof (New Zealand Sociology, 2025)
Universities have Queer staff and students and conduct Queer research, so are they Queer institutions themselves? Can universities be ‘safe spaces’ for Rainbow Communities? Unfortunately, there is insufficient data in Aotearoa/New Zealand to be able to conclusively test that, so the historical and contemporary relationships with and treatment and experiences at university of women, Māori and Pacific Peoples are considered as alternatives for those with Rainbow Communities. For each of these marginalised groups, similar patterns of oppression and discrimination present through consistent lack of career progression, pay equity and representation in senior leadership, short-term and precarious employment, harassment and violence, and sidelining into small and out-of-the-way departments and disciplines held in lower validity to ‘traditional’ subjects. However, scholars from these communities are forming their own research and support networks which are inclusive, intersectional and interdisciplinary. Within this framework of bottom-up initiatives, universities could be Queer institutions in the same way that they could be feminist and Indigenous institutions. It is entirely possible—but may involve rebuilding our institutions from the ground up rather than applying a new coat of paint.